IMPLEMENTASI PROGRAM MBG DALAM PENANAMAN KARAKTER RELIGIUS KELOMPOK B DI RA AL – IZZAH KOTA SERANG - Ninis Dwi Nurhaeny; Isti Rusdiyani; Siti Khosiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the MBG Program in fostering religious character among Group B at RA Al-Izzah in Serang City. This study employs a descriptive qualitative approach. Data collection techniques were conducted through observation, in-depth interviews with teachers and the principal, documentation, and field notes. Data analysis referred to the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that the implementation of MBG at RA Al-Izzah has been carried out in a structured and integrated manner within daily routines, encompassing the planning, implementation, and evaluation stages in accordance with the school’s Standard Operating Procedures (SOP). Through shared school meals, the program successfully instilled six core religious character values: prayer, gratitude, discipline, responsibility, proper table manners, and social compassion. Factors supporting the program’s success include foundation support (self-sufficient kitchen), strong team collaboration, adequate facilities, appealing menus, and collaboration with parents. Meanwhile, the main barriers are children’s food preferences (particularly refusal to eat vegetables), menu monotony, and budget constraints. The school overcomes these challenges through a non-coercive, persuasive approach, consistent habit-building, and providing feedback to service providers to improve menu variety. It is concluded that the MBG Program at RA Al – Izzah not only serves to meet nutritional needs but has transformed into a meaningful, effective, and sustainable medium for religious character education for early childhood. Keywords: Implementation, MBG, Religious Character, Early Childhood Education